PENERAPAN SIMPLE NETWORK MANAGEMENT PROTOCOL PADA FCAPS UNTUK MONITORING SERVER BERBASIS ANDROID STUDI KASUS PT JARING SYNERGI MANDIRI - Muhammad Solehfuddin; Sugiyono Sugiyono; Muryan Awaludin (CKI ON SPOT, 2016)
Along with advances in network technology and computer today it becomes role with various groups likes students, academics, and offices. Usage of network technology and computer will be more intensive with many kind of devices connects to the servers. As we knows that servers have important roles within network, otherwise we need tools to determine performance of the servers. PT Jaring Synergi Mandiri is company that provide services such as call center services for 24 hours. With IT support as administrator of systems to ensure business process to running well continues. Application network monitoring and server at this time just effective when IT support at the office. The problems will be occur when IT support at the outside office, server and network status can’t be known so that repair process will be hampered. Based on these condition, researchers will give recommend to build application network monitoring for smartphone (Android) as tools to review remote monitor using VPN so it can be access from anywhere and anytime. The researchers had obtained data to be analyzed and described as UML using software Modelio. By using SDLC method that include planning, analysis, design, implementation and maintenance.Keywords: Remote VPN, Server Monitoring, Android